The Flame of Eternity : An Interpretation of Nietzsche's Thought - Michalski, Krzysztof (Book collections on Project MUSE., 2011)
The Flame of Eternity provides a reexamination and new interpretation of Nietzsche's philosophy and the central role that the concepts of eternity and time, as he understood them, played in it. According to Krzysztof Michalski, Nietzsche's reflections on human life are inextricably linked to time, which in turn cannot be conceived of without eternity. Eternity is a measure of time, but also, Michalski argues, something Nietzsche viewed, first and foremost, as a physiological concept having to do with the body. The body ages and decays, involving us in a confrontation with our eventual death.